Juridical Analysis of the Balance of Legal Protection Between Workers and Employers in the Indonesian Labor Law System - Vryacaka Jauzaak Olivia (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to analyze the extent to which labor law in Indonesia is able to create a balance of legal protection between workers and employers, as well as to identify the factors influencing such balance. This research employs a normative juridical method with statutory and conceptual approaches. The results indicate that, normatively, Indonesian labor law—particularly Law Number 13 of 2003 on Manpower and Law Number 11 of 2020 on Job Creation—has been designed to establish fair and balanced employment relations. However, in practice, there is a tendency for legal protection to be more heavily oriented toward workers, resulting in limited flexibility and increased compliance burdens for employers. Furthermore, this balance is influenced by several factors, including legal policy orientation, economic conditions, regulatory complexity, effectiveness of law enforcement, and globalization dynamics. Therefore, a more proportional legal policy is needed to achieve an ideal balance in industrial relations.